Predictors of delirium after cardiac surgery in patients with sleep disordered breathing. Issue 2 (8th August 2019) - Tafelmeier, Maria; Knapp, Marvin; Lebek, Simon; Floerchinger, Bernhard; Camboni, Daniele; Creutzenberg, Marcus; Wittmann, Sigrid; Zeman, Florian; Schmid, Christof; Maier, Lars Siegfried; Wagner, Stefan; Arzt, Michael
Introduction: Delirium ranks among the most common complications after cardiac surgery. Although various risk factors have been identified, the association between sleep disordered breathing (SDB) and delirium has barely been examined so far. Here, our objectives were to determine the incidence of post-operative delirium and to identify the risk factors for delirium in patients with and without SDB. Methods: This subanalysis of the ongoing prospective observational study CONSIDER-AF (ClinicalTrials.gov identifier NCT02877745) examined risk factors for delirium in 141 patients undergoing cardiac surgery. The presence and type of SDB were assessed with a portable SDB monitor the night before surgery. Delirium was prospectively assessed with the validated Confusion Assessment Method for the Intensive Care Unit on the day of extubation and for a maximum of 3 days. Results: Delirium was diagnosed in 23% of patients: in 16% of patients without SDB, in 13% with obstructive sleep apnoea and in 49% with central sleep apnoea. Multivariable logistic regression analysis showed that delirium was independently associated with age ≥70 years (OR 5.63, 95% CI 1.79–17.68; p=0.003), central sleep apnoea (OR 4.99, 95% CI 1.41–17.69; p=0.013) and heart failure (OR 3.3, 95% CI 1.06–10.35; p=0.039). Length of hospital stay and time spent in the intensive care unit/intermediate care setting were significantly longer for patients with delirium. Conclusions: Among the established risk factors for delirium, central sleep apnoea was independently associated with delirium. Our findings contribute to identifying patients at high risk of developing post-operative delirium who may benefit from intensified delirium prevention strategies. This prospective observational study shows that, among established risk factors, central sleep apnoea is independently associated with post-operative delirium in patients undergoing elective cardiac surgery http://bit.ly/2LPsrSp